Profit Driven Decision Assist System to Select Efficient IaaS Providers - Mohan Murthy MK; Sanjay HA; Supreeth BM (International Journal of Electrical and Computer Engineering (IJECE), 2018)
IaaS providers provide infrastructure to the end users with various pricing schemes and models. They provide different types of virtual machines (small, medium, large, etc.). Since each IaaS provider uses their own pricing schemes and models, price varies from one provider to the other for the same requirements. To select a best IaaS provider, the end users need to consider various parameters such as SLA, pricing models/schemes, VM heterogeneity, etc. Since many parameters are involved, selecting an efficient IaaS provider is a challenging job for an end user. To address this issue, in this work we have designed, implemented and tested a decision-assist system which assists the end users to select efficient IaaS provider(s). Our decision-assist system consists of an analytical model to calculate the cost and decision strategies to assist the end user in selecting the efficient IaaS provider(s). The decision assist system considers various relevant parameters such as VM configuration, price, availability, etc. to decide the efficient IaaS provider(s). Rigorous experiments have been conducted by emulating various IaaS providers, and we have observed that our DAS successfully suggests the efficient IaaS provider/ providers by considering the input parameters given by the user.